2019
DOI: 10.1063/1.5123208
|View full text |Cite
|
Sign up to set email alerts
|

Improved space charge suppression in PP/SEBS nanocomposites by controlling MgO nanoparticles with abundant surface defects

Abstract: Polymer nanocomposite dielectrics have received extensive attention in the field of electrical materials and equipment. Studies have shown that the interface region between the nanoparticles and polymer matrix has an important influence on the properties of nanocomposites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Specially, the tensile strength and elongation at break of PP/SEBS blends are also improved by loading 0.5 phr flower‐MgO, showing potential for the optimisation of power cable insulation. They also synthesised MgO nanoparticles with abundant surface defects (C‐MgO) containing a highly effective interface by surface carbonisation, which can realise the enhancement of electrical and mechanical properties with about 0.2 phr doping content [126]. Moreover, multi‐dimensional zinc oxide composite fillers (co‐ZnO) is also used to achieve the suppression of space charge accumulation and the enhancing of breakdown strength [127].…”
Section: Research Status Of Polypropylene Modification Based On Struc...mentioning
confidence: 99%
“…Specially, the tensile strength and elongation at break of PP/SEBS blends are also improved by loading 0.5 phr flower‐MgO, showing potential for the optimisation of power cable insulation. They also synthesised MgO nanoparticles with abundant surface defects (C‐MgO) containing a highly effective interface by surface carbonisation, which can realise the enhancement of electrical and mechanical properties with about 0.2 phr doping content [126]. Moreover, multi‐dimensional zinc oxide composite fillers (co‐ZnO) is also used to achieve the suppression of space charge accumulation and the enhancing of breakdown strength [127].…”
Section: Research Status Of Polypropylene Modification Based On Struc...mentioning
confidence: 99%
“…[10][11][12] At present, the modification methods for PP can be divided into two categories: chemical [13][14][15][16] and physical modification. [17][18][19][20][21] Commonly used chemical modifications are copolymerization 13,14 and grafting modification, 15,16 and so on. Huang et al compared the mechanical and electrical properties of six kinds of propylene copolymers and found that the comprehensive performance of ethylene-propylene copolymers are the best.…”
Section: Introductionmentioning
confidence: 99%
“…So far, two kinds of important methods that have been proposed to enhance the breakdown field strength of polymers have mainly focused on the incorporation of nanofillers and voltage stabilizers. 15 18 It has been reported that the mechanism by which low content nanofillers (such as TiO 2 , 19 , 20 MgO, 21 , 22 and Al 2 O 3 23 , 24 ) can improve the breakdown strength of polymer is mainly attributed to two ways: (1) the tortuous path of electron breakdown caused by nanofillers. 25 , 26 (2) Nanofillers capture electrons by introducing deep traps into the polymer ( Figure 1 b).…”
Section: Introductionmentioning
confidence: 99%
“…So far, two kinds of important methods that have been proposed to enhance the breakdown field strength of polymers have mainly focused on the incorporation of nanofillers and voltage stabilizers. It has been reported that the mechanism by which low content nanofillers (such as TiO 2 , , MgO, , and Al 2 O 3 , ) can improve the breakdown strength of polymer is mainly attributed to two ways: (1) the tortuous path of electron breakdown caused by nanofillers. , (2) Nanofillers capture electrons by introducing deep traps into the polymer (Figure b). It has been revealed that nano-SiO 2 can effectively improve the electrical insulation properties of polymers. ,, However, it is difficult for supersurficial nano-SiO 2 to disperse uniformly in the polymer, so the expected performance cannot be obtained.…”
Section: Introductionmentioning
confidence: 99%